Associations of 1, 5-Anhydroglucitol and 2-Hour Glucose with Major Clinical Outcomes in the Atherosclerosis Risk in Communities (ARIC) Study. (12th June 2020) - Warren, Bethany; Lee, Alexandra K; Ballantyne, Christie M; Hoogeveen, Ron C; Pankow, James S; Grams, Morgan E; Köttgen, Anna; Selvin, Elizabeth
Abstract: Background: 1, 5-Anhydroglucitol (1, 5-AG) is a novel biomarker of glycemic control proposed to monitor recent hyperglycemic excursions in persons with diabetes. The clinical utility of 1, 5-AG outside of diagnosed diabetes is unclear, but it may identify people at high risk for diabetes and its complications. We compared associations of 1, 5-AG with 2-h glucose for risk of major clinical complications. Research Design and Methods: We prospectively followed 6644 Atherosclerosis Risk in Communities (ARIC) Study participants without diagnosed diabetes for incident diagnosed diabetes, chronic kidney disease, cardiovascular disease, and all-cause mortality for ∼20 years. We assessed associations of 1, 5-AG and 2-h glucose (modeled categorically and continuously with restricted cubic splines) with adverse outcomes using Cox models and evaluated improvement in risk discrimination using Harrell's c-statistic. Results: 1, 5-AG <10 µg/mL was statistically significantly associated with incident diabetes (HR: 2.70, 95% CI 2.31, 3.15), and showed suggestion of association with the other outcomes compared to 1, 5-AG ≥10 µg/mL. Continuous associations of 1, 5-AG with outcomes displayed a clear threshold effect, with risk associations generally observed only <10 µg/mL. Comparing associations of 1, 5-AG and 2-h glucose with outcomes resulted in larger c-statistics for 2-h glucose than 1, 5-AG for all outcomes (difference in c-statistic [2-h glucose -1, 5-AG] for diagnosed diabetes: 0.17 [95%CI, 0.15, 0.19]; chronic kidney disease 0.02 [95%CI 0.00, 0.05]; cardiovascular disease 0.03 [95%CI, 0.00, 0.06]; and all-cause mortality 0.04 [95%CI, 0.02, 0.06]). Conclusions: In this community-based population without diagnosed diabetes, low 1, 5-AG was modestly associated with major clinical outcomes and did not outperform 2-h glucose.